Demokrasi Indonesia Masa Kepemimpinan Presiden Jokowi-Amin Periode 2019-2024 - Saiman (Public Sphere Review, 2023)
Launch of 2020 Indonesian Ombudsman Annual Report on Monday 8 February 2021, President Joko Widodo said "public be active in conveying criticism, input, or potential maladministration.â€ Public service providers continue to increase efforts improvements. On the other hand, President's statement is very contradictory or contrary to socio-political and democratic developments society occurred Jokowi became President of Indonesia for 2nd period in 2019-2024. Several socio-political events that occurred showed democratic process in Indonesia experienced shift or decreased percentage. This paper describes and analyzes development of Indonesian democracy during leadership of President Joko Widodo Period II and factors decline development of democracy in Indonesia. This paper uses reference studies and documentation data collection techniques, sources, and uses a qualitative descriptive analysis of development democracy in Indonesia during President Jokowi's second period. The results of study found and according to Compas research until October 7 2022, that a decline development of democracy in Indonesia, decrease in public trust in performance of Jokowi-Amin Government field of law enforcement, only at 51.5%. Achievement is down compared to the results of previous survey in June 2022. The economic sector is only 50.8% to rising prices of basic commodities which continue increase. Eventhough, social welfare sector is still 74% is possibility to be temporary, because BLT has been disbursed community, political and security sector 74.6%, increasing lack of response or (bored) public response socio-political situation dominated by political party activities 2024 election.